Comparative Evaluation of Clinical Efficacy of Ambu AuraGain™ Disposable Laryngeal Mask with i-gel™ for ventilation in paediatric patients undergoing elective surgery under general anaesthesia - Jakhar, Varsha; Aggarwal, Nidhi; Krishna, Bhavya (Journal of the Portuguese Society of Anesthesiology, 2024)
Objective: This prospective interventional randomised single-blinded comparative study aimed to evaluate the clinical efficacy of Ambu AuraGain™ and i-gel™ as supraglottic airway devices for controlled ventilation in paediatric patients undergoing elective surgical procedures under general anaesthesia. Methods: The study included 80 children aged between 2 and 10 years, weighing between 10 to 30 kg, and classified as ASA Physical Status I and II. Children with anticipated difficult airways, high risk of aspiration, or respiratory tract infections were excluded. Participants were randomly assigned to either Group A (Ambu AuraGain™) or Group I (i-gel™). The primary outcome was the measurement of oropharyngeal seal pressure (OSP) at 5 and 10 minutes post device insertion. Secondary outcomes involved evaluating insertion characteristics, fiberoptic bronchoscope views, ventilatory parameters, hemodynamic variables, and complications. Results: The mean OSP was significantly higher in the Group A compared to the Group I at 5 minutes (24.70±2.29 cmH2O vs. 23.65±3.14 cmH2O) and 10 minutes (26.48±2.53 cmH2O vs. 25.23±2.66 cmH2O). Group A also took significantly longer to achieve an effective airway. The initial success rate, insertion features, and gastric tube insertion showed no significant differences between the groups. Fiberoptic bronchoscope view scores differed significantly, favouring Ambu AuraGain™. Ventilatory parameters, hemodynamic variables, and postoperative pharyngolaryngeal morbidity did not show any significant differences between the two groups. Conclusion: Ambu AuraGain™ could be a preferable option for controlled ventilation in the paediatric patients undergoing elective surgery under general anaesthesia compared to i-gel™. However, additional research is required to confirm these findings and investigate other clinical factors.